Disturbed cofactor binding by a novel mutation in UDP-galactose 4′-epimerase results in a type III galactosemia phenotype at birth. Issue 21 (10th February 2016) - Paul, Stephanie; McCorvie, Thomas J.; Zschocke, Johannes; Timson, David J.
Abstract : The p.A89V variant of UDP-galactose 4′-epimerase (GALE) is less stable and has lower affinity for the NAD + cofactor than the wild-type enzyme. Abstract : UDP-galactose 4′-epimerase (GALE) is an essential enzyme in galactose metabolism and its dysfunction results in type III galactosemia. Herein we report a patient born with abnormal blood galactose levels and reduced GALE activity who was shown to be heterozygous for a c.266C>T missense mutation in the GALE gene, predicted to result in the amino acid exchange p.A89V. Over a period of months, the patient's blood galactose, galactose 1-phosphate and GALE activity levels reverted to normal, encouraging us to investigate this mutation. Structurally Ala89 is a highly conserved residue located close to the binding site of the cofactor, NAD + . Consequentially molecular modelling predicted that this mutation results in steric clashes between the cofactor and valine side chain, and bioinformatic predictions suggested that p.A89V is likely to be less stable than the wild-type. Biochemical studies on the recombinant p.A89V enzyme demonstrated lower activity than the wild type ( K m increased by approximately 30-fold; k cat reduced approximately 180-fold), and additionally changes in stability and altered NAD + binding were observed. Thus, a picture emerges in which this mutation leads to reduced stability, disturbed cofactor binding and subsequently reduced activity. Overall this study suggests that bioinformatics predictions are useful in assessing the effects of newly discovered mutations on enzyme function, but care should be taken in extending predictions to the clinical phenotype especially in cases of heterozygosity. It also raises interesting questions about a dominant negative effect of some GALE missense alleles and potential compensatory mechanisms occurring in people born with clinical chemistry measurements suggesting a diagnosis of galactosemia.